METODE PEMBIASAAN DALAM RANGKA MENINGKATKAN KEMANDIRIAN ANAK DI TK ASH SHOLIHIN SURABAYA TAHUN AJARAN 2022/2023 - Masluchah, Luluk (MOTORIC, 2024)
This research is based on pre-observations in the field, namely interviews with several parents of students, there are still many children who are still carrying out activities assisted by their parents, for example homework from schools that are done by parents. The purpose of this study is to develop early childhood independence in Ash Sholihin Kindergarten by using the habituation method. The research conducted is a type of descriptive qualitative research with data collection techniques through observation and interviews. The independence of children in Ash Sholihin Kindergarten is developed through habituation methods which are carried out continuously. The method that can support children's independence is the habituation method. With the use of this habituation method, the independence of children in Ash Sholihin Kindergarten has started to develop. This can be seen from the daily life of children at school, throwing trash in its place, wearing their own shoes without the help of the teacher, eating alone without the help of others, daring to come to school alone without being watched over. by his parents.